KURIKULUM KULLIYATUL MU’ALLIMIN AL-ISLAMIYAH (KMI) GONTOR SEBAGAI MODEL INOVASI KURIKULUM DI TENGAH ARUS MODERNISASI PENDIDIKAN: The Curriculum of Kulliyatul Mu’allimin Al-Islamiyah (KMI) Gontor as a Model of Curriculum Innovation Amidst the Trend Toward the Modernization of Education - Mardiyah; Najwa Sajida El Yunusi; Nasruddin (TA'LIMUNA: Jurnal Pendidikan Islam, 2026)
This article aims to explore curriculum innovation amid the trend of educational modernization based on the curriculum of Kulliyatul Mu’allimin Al-Islamiyah (KMI) at the Gontor Islamic Boarding School in Ponorogo, East Java. The method employed is a historical approach (historiography) through a literature review. The primary data source is a book by Kiai Dr. A. Syukri Zarkasyi titled Gontor and the Renewal of Pesantren Education. Secondary data sources come from various relevant references. The data is then analyzed and described to form an innovative curriculum concept. From the time Indonesia was still in a state of chaos before independence, up to the post-independence era today, the Gontor Islamic Boarding School has participated in revitalizing the Educational Renaissance in Indonesia through the innovation of the KMI curriculum, whose graduation certificates were recognized by Egypt, Malaysia, and Pakistan before being officially recognized by the Indonesian government. Artikel ini bertujuan mengembangkan inovasi kurikulum di tengah arus modernisasi pendidikan berdasarkan Kurikukum Kulliyatul Mu’allimin Al-Islamiyah (KMI) Pesantren Gontor Ponorogo Jawa Timur. Metode yang digunakan adalah pendekatan sejarah (historiografi) melalui studi pustaka. Sumber data primernya adalah buku karya Kiai Dr. A. Syukri Zarkasyi yang berjudul Gontor dan Pembaruan Pendidikan Pesantren. Sumber data sekundernya dari berbagai referensi yang relevan. Lalu data dianalisis dan dideskripsikan menjadi konsep kurikulum inovatif. Sejak Indonesia masih dalam kondisi carut-marut sebelum masa kemerdekaan, hingga pasca kemerdekaan saat ini, Pesantren Gontor telah berpartisipasi dalam menyemarakkan Kebangkitan Pendidikan di Indonesia melalui inovasi kurikulum KMI yang ijazah lulusnya diakui oleh negara Mesir, Malaysia dan Pakistan, sebelum diakui secara resmi oleh negara Indonesia.  Kata Kunci : KMI Gontor; Kurikulum; Modernisasi; Pesantren.